Andrew Lewis Aycock - Grigg Studio; Grigg Studio (Z. Smith Reynolds Library, 1920)
ca.1960
Wake Forest University Professor A. Lewis Aycock in the Admissions Office. Aycock was Professor of English 1920-1971; Professor of Art 1968-1971; Director of Admissions 1957-1959.
Keywords: Forsyth County (N.C.) -- History -- Sources; Aycock, Andrew Lewis; Digital Forsyth; Forsyth County (N.C.) -- History -- Pictorial works